Embalando sons e seduzindo o olhar: a argumentação nas capas de discos da Tropicália - Soares, Delzio Marques (2019)
The 12-inch vinyl record (LP) was the music industry's main media in the 20th century. In this context, the cover that wrapped the disc, articulating argumentative elements through graphic design, promoted the product and collaborated in the adhesion to a new musical proposal. The corpus of this study includes the covers of seven LPs from Tropicália, a musical movement led by the artists Caetano Veloso and Gilberto Gil, who flourished between October 1967 and December 1968. Considering the cover as a discourse, the general objective of the research is to understand which way the covers of these LPs corroborate the musical proposal of the movement. As a specific objective, it demonstrates what argumentative resources were used in their graphic projects. The theoretical foundations of Rhetoric - as systematized by Aristotle (2012) and extended by modern thinkers such as Reboul (1998) and Tringali (2014) - supported this study, as well as concepts of the New Rhetoric of Perelman and Olbrechts-Tyteca (2014). The visual literacy primer proposed by Dondis (2015), provided us with tools for understanding visual language, in conjunction with Barthes's (2015) notions of Image Rhetoric. At the confluence of the New Rhetoric with Graphic Design, we adopted the analysis tool proposed by Almeida Junior and Nojima (2010). This investigation seems relevant to us, considering the little that has been dedicated to the visual language and its argumentative possibilities in the scope of linguistic studies, especially with the object of record cover. We consider that our objective was reached, because, through the analyzes of the corpus, we could perceive the argumentative resources of the seven covers, so that six of them corroborate the tropicalist ethos, and one of them does not.